Effect of Web-Based She Smart Education Models on Adolescent Girl's Knowledge, Attitudes, and Practice about Obesity. (2022) - Herliah, A.; Baso, Yusring Sanusi; Hidayanty, Healthy; Syarif, Syafruddin; Aminuddin, Aminuddin; Bahar, Burhanuddin
No abstract available